2009
DOI: 10.1016/s1472-6483(10)60092-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual ovarian volumes obtained from 2-dimensional and 3-dimensional ultrasound lack precision

Abstract: Measuring ovarian volume has been suggested as a possible screening test to assess a woman's ovarian reserve. For such a screening tool to be clinically useful, knowledge of its precision and reproducibility is essential. Recent advances in ultrasound scanning techniques allow the measurement of volumes in three dimensions rather than the traditional estimation from two dimensions. Transvaginal 2-dimensional (2D) and 3-dimensional (3D) ultrasound examinations were performed on 49 women attending a tertiary cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This finding is compatible with that reported by Brett et al , who demonstrated a lack of precision in ovarian volume measurement by 2D and 3D ultrasound, which overestimate ovarian volumes [22]. The authors advise that the possibility of error should be taken into account when making clinical decisions.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is compatible with that reported by Brett et al , who demonstrated a lack of precision in ovarian volume measurement by 2D and 3D ultrasound, which overestimate ovarian volumes [22]. The authors advise that the possibility of error should be taken into account when making clinical decisions.…”
Section: Discussionsupporting
confidence: 91%
“…14 Similar to our study, Brett et al reported high degree of ICC of intra- and inter- observer variability for ovarian volume measurements. 24 However, the authors also proved that both methods were lacking from good inter- and intra- observer variability, particularly when estimating low ovarian volumes. In our study, 2D intra-observer variability was particularly poor when measuring smaller adrenal glands.…”
Section: Discussionmentioning
confidence: 94%
“…The weakness is the heterogeneity of the values obtained from diverse sources. We cannot be certain that the measurement of ovarian volume by abdominal ultrasound, which is often difficult in young children, is as accurate as measurement by transvaginal ultrasound in older females [28]. Similarly measurements taken at MRI may be different from those obtained by weighing the ovary following oophorectomy and calculating the volume from weight.…”
Section: Discussionmentioning
confidence: 97%